2014
DOI: 10.1007/s00705-014-1981-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of LIGHT expression plasmid enhances humoral and cellular immune responses to HIV-1 Nef in mice

Abstract: The immunogenicity and efficacy of a DNA vaccine can be greatly enhanced when a gene adjuvant is used. LIGHT, a member of TNF superfamily, can function as a costimulatory molecule for human naïve T cells to proliferate and can be a potential gene adjuvant. In the current study, the eukaryotic expression plasmid pcDNA-nef was constructed by inserting a full-length nef gene into pcDNA3.1(+), and an in vitro transfection experiment suggested that the nef gene could be expressed successfully in mammalian cells. BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thus, development of new-generation vaccines is necessary to control PCV2 infection. Direct injection of plasmid DNA has been used as a promising approach to protect animals and humans against pathogens (34,35). DNA vaccines against PCV2 have been investigated, which often have limited efficacy and need two or three immunizations to achieve a good level of immunity (1,3,8).…”
mentioning
confidence: 99%
“…Thus, development of new-generation vaccines is necessary to control PCV2 infection. Direct injection of plasmid DNA has been used as a promising approach to protect animals and humans against pathogens (34,35). DNA vaccines against PCV2 have been investigated, which often have limited efficacy and need two or three immunizations to achieve a good level of immunity (1,3,8).…”
mentioning
confidence: 99%
“…However, the issue of finding complementary or alternative treatment and prevention strategies still persists. Among numerous HIV genes examined for generation of immunogenic recombinant DNA and proteins, the highly-conserved HIV-1 accessory protein Nef has been widely regarded as a highly immunogenic candidate for development of therapeutic vaccines (14)(15)(16)(17). This is mainly attributed to the main role of Nef in HIV pathogenesis via downregulation of cell-surface expression of multiple membrane-associated proteins, enhancement of virion infectivity, stimulation of viral replication, interference of cellular 15/ Nikyar and colleagues polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…signal transduction, and manipulation of the apoptosis mechanism (14). On the other hand, Vpr has been known as a crucial component of HIV pathogenicity and progression.…”
Section: Pcr-amplified Vpr Fragment Was Cloned Intomentioning
confidence: 99%
“…One study indicated that anti-Nef antibodies in mice immunized with pBN-Nef were detected within four weeks after the last immunization, whereas mice immunized with pCGE2-Nef had poor anti-Nef antibodies (45). Other data showed that HIV-1 Nef DNA vaccine (pcDNA-Nef) could induce anti-Nef antibodies and Nef-specifi c CTL activity, but stronger specifi c immune responses were stimulated in mice receiving pcDNA-Nef along with LIGHT expression plasmid (LIGHT, a member of TNF superfamily), suggesting that the LIGHT could be considered as a gene adjuvant for HIV-1 DNA vaccination (46). Herein, we also showed that Gp96 as an adjuvant could increase immune responses induced by pcDNA-Nef regimen.…”
Section: Discussionmentioning
confidence: 99%